THE INFLUENCE OF HOMEWORK ON STUDENTS’ READING SKILL AT THE ELEVENTH GRADE STUDENTS OF SMA AL AZHAR 3 BANDAR LAMPUNG - Desi Ike Sari; Susanto Susanto (Universitas Bandar Lampung, 2016)
The objective of this research is to find out the influence of homework on students’ reading skill at the eleventh grade students of SMA Al Azhar 3 Bandar Lampung Academic year 2016/2017. Homework was used to help students understanding in Reading skill. By giving homework to the students, they will have more time in understanding the text. The data were collected by giving two pre-test and post-test to experimental and control group. The treatment was giving homework in reading text in every meeting for experimental group while in control group students just doing class work. Data analysis was attempted by using T-test for two-group design.The result indicate that p-value 0.05 = 1.9944, 0.01 = 2.6479 and t-value = 3.09. It means that p-value is smaller than t-value. Therefore, hypothesis testing showed that null hypothesis (Ho) was rejected and alternative hypothesis (Ha) was accepted. Thus, the students achievement of giving homework are higher that the students’ achievement of doing class work. It can be concluded that giving homework to the students was influence their reading skill. By giving homework to the students’ reading skill, they have more time in understanding the text. In the other hand, the teacher should have coordination in giving homework, so the students will not feel frustrated because usually they have a lot of home work every night.